Article Key Performance Indicators of Indonesia State-Owned Enterprise - a Model Using BSC and MBPE - Sulistyo, Budi; Darmayana, Riandi Aditia (International Journal of Integrated Engineering, 2020)
The State-Owned Enterprise (SOE) in Indonesia should report financial and non-financial information to the stockholder, the government. For these reasons, the government published a performance measurement system to stimulate SOEs improving their quality and productivity namely KPKU, which adapted from Malcom Baldrige for Performance Excellence (MBPE) Criteria. However, there is no description of how to deploy this measurement system into performance measurement for the SOEs. Therefore, this paper looks at designing the key performance indicators of the State-Owned Enterprise by using Balanced Scorecard (BSC) interrelated to MBPE Criteria. This study explored the vision and mission of the SOE and analysed the relationship to the government requirements to formulate the company's strategic plan. The strategies translated into four balanced scorecard perspectives which interrelated to Baldrige Criteria. To measure the strategic achievement, we formulate the key performance indicators (KPI) for each strategic objective.